COLOURED GILL NETS FOR RESERVOIR FISHING - NARAYANAPPA, G; KHAN, A A; NAIDU, R M (Fishery Technology, 2017)
Experimental fishing with different coloured nets has shownthat white net yields better catch. The efficiency of thecoloured nets was in the order yellow, grey, green and blue.Though there is little evidence to show some species preferenceto a particular colour, the results wne not conclusive as theanalysis of variance indicated that interaction between speciesand colour is significant only at 5% level.